Pencegahan dan Penanganan Tindak Kekerasan Terhadap Anak oleh Dinas Pemberdayaan Perempuan, Perlindungan Anak, Pengendalian Penduduk dan Keluarga Berencana (DP3KB) di Kabupaten Bintan - Dini Oktavia Putri; Wanda Hafisya; Mahesa Arya Pratama (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Child abuse in Indonesia, particularly in Bintan, shows a concerning upward trend. This study aims to analyze the efforts of the Women's Empowerment, Child Protection, Population Control, and Family Planning Agency (DP3KB) in preventing and addressing cases of violence against children. The research method employed is empirical research, collecting primary data through interviews and observations, as well as secondary data from relevant literature. Findings indicate that DP3KB has implemented prevention programs that include socialization of children's rights and campaigns for reporting violence, although it still faces challenges such as limited resources and lack of inter-agency coordination. The implications of this research highlight the importance of cross-sector collaboration and increased community awareness to protect children from violence. By understanding the steps taken by DP3KB, it is hoped that this can contribute to child protection efforts and the handling of violence cases in Bintan Regency.